Veloz como un grillo - Wood, Audrey; Wood, Don, 1945- (New York, N.Y. : Child's Play (International), 1993)
A young boy describes himself as "loud as a lion," "quiet as a clam," "tough as a rhino," and "gentle as a lamb."
Title and dates vary
Accelerated Reader
Keywords: Self-perception -- Juvenile fiction; Animals -- Juvenile fiction; Stories in rhyme -- Juvenile literature